Laryngeal synovial sarcoma: Report of 2 cases - Mouna Bellakhdhar; Amira Cheniti; Monia Ghammem; Ahlem Bdioui; Sarra Mestiri; Abir Meherzi; Wassim Kermani; Mohamed Abdelkefi (Journal of the Egyptian National Cancer Institute, 2018)
Synovial sarcoma is a malignant mesenchymal tumor. It most commonly occurs in the lower extremities of young adults. The head and neck are rare sites, accounting for less than 10%. The larynx is an extremely rare site.We report two cases of 27 and 18 year-old men who developed a synovial sarcoma of the larynx. They presented with hoarseness of voice and hemoptysis. Endoscopy detected a mass in the supraglottic region. The biopsy concluded a synovial sarcoma. Immunohistochemistry conveyed diagnostic certainty. They had been treated with total laryngectomy and post-operative radiotherapy. The 2 patients are seen for regular follow-ups in our department and they remained recurrence-free for 10 years and 24 months, respectively.Synovial sarcoma is a very rare tumor of the larynx. A multidisciplinary therapeutic approach is essential for the management of this malignancy. Long-term follow-up is required to monitor for recurrence and improve disease-free survival. Keywords: Synovial sarcoma, Larynx, Head and neck